2007
DOI: 10.2215/cjn.04101206
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease

Abstract: Cardiovascular disease is a major source of morbidity and mortality for patients with chronic kidney disease (CKD). Peripheral arterial disease (PAD) is a strong predictor of coronary artery disease and a risk factor for mortality in the general population. This is of particular interest to nephrologists because the risk for PAD is increased in CKD. Often, PAD is overlooked as a source of morbidity and as a cardiovascular risk factor in this population. This review serves as an overview of the epidemiology, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 74 publications
3
55
0
Order By: Relevance
“…In this study, PAD assessed on duplex US was significantly associated with older age, diabetes, smoking, decrease in Kt/V, increase in serum total cholesterol levels, and other atherosclerotic comorbidities. These associations are consistent with previous reports among hemodialysis patients (12,20,26,28). This study showed that asymptomatic PAD was 23.8% in hemodialysis patients recruited from an outpatient dialysis unit.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, PAD assessed on duplex US was significantly associated with older age, diabetes, smoking, decrease in Kt/V, increase in serum total cholesterol levels, and other atherosclerotic comorbidities. These associations are consistent with previous reports among hemodialysis patients (12,20,26,28). This study showed that asymptomatic PAD was 23.8% in hemodialysis patients recruited from an outpatient dialysis unit.…”
Section: Discussionsupporting
confidence: 93%
“…However, duplex US is safe, inexpensive, and accurate enough to assess PAD in clinical settings (25,26). Patients with impaired kidney function are at increased risk for gadolinium-associated nephrogenic systemic fibrosis (26,27). In this study, PAD assessed on duplex US was significantly associated with older age, diabetes, smoking, decrease in Kt/V, increase in serum total cholesterol levels, and other atherosclerotic comorbidities.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As described elsewhere, [2,18] hemodialysis patients are known to have general atherosclerotic disease with high prevalence of peripheral arterial occlusive disease (PAOD) and amputations. According to our data, the hemodialysis procedure can contribute to the impairment of peripheral microcirculation and peripheral ischemia together with PAOD.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Vascular repair mechanisms in patients with CKD are poorly understood. Bone marrowderived endothelial progenitor cells (EPCs) are involved in the reparative processes of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%